Contributions to the elucidation of a controversial episode. The Ciulei Case. (2) - Liviu CORCIU (Bulletin of "Carol I" National Defense University)
Based on previous documentation, not necessarily the subject of this article, we can state that the administration of military justice in the War of the Integration was not a perfect process, among the most important criticisms being the judicial errors recorded, on the one hand, and the interference of commanders in the act of justice, on the other. The fact that the members of court martial panels were appointed by the commanders of the major units with which they operated, from the divisional level upwards, was a procedure that naturally facilitated the existence of subordination relationships, with a direct effect on the administration of justice. Another explanation for the low quality of justice is the lack of specialized training of the members of the councils of war and courts-martial, the training of the officers called upon to carry out military justice being encumbered by the educational system of the time. It is in this context that the trial of Second Lieutenant Constantin Ciulei should also be analyzed, which thus takes on new meanings and significance. The disciplinary situation of the troops called for an exemplary punishment, which was swiftly carried out and significantly impressed the audience, and the fact that Ciulei was an officer was an asset that ensured the notoriety of the event.